Frequency of use of the digital services in the library of the university polyclinic “Central Electronuclear” - María de los Reyes González Ramos; María Elinor Dulzaides Iglesias; Domingo Pérez Valladares; Martha Vázquez Villavicencio (Medisur)
Background: Information and Communication Technologies (ICT) have pushed the evolution of library services and encouraged the development of libraries in the Primary Health Care System in Cuba, with the establishment of digital services. Objective: To determine the frequency of use of the digital services provided by the library of the university polyclinic " Central Electronuclear " in Cienfuegos. Methods: A descriptive study conducted during 2007, including a sample of 141 potential users of the library. The following variables were measured: users categories and use of the different digital services and perception of quality of those services. Results: the category of users who mostly use the digital services proved to be the professionals with 50%. The most commonly used digital services are the health intranet and the e-mail, with 97, 9 and 96%, 5%, in that order. The least used is the online reference, with 85.1%. Conclusions: the digital services of the library of the university polyclinic "Central Electronuclear " reach a high use frequency.